2019
DOI: 10.1142/s021968671950001x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Conceptual Framework of Lean Construction Principles: An Input–Output Model

Abstract: In the new global economy, Lean Construction has become an effective way to design construction systems, which aims at reducing all forms of waste and creating the maximum of value for the customer. However, previous studies have reported that there are various implementation approaches, and most construction practitioners have applied this management philosophy according to their own understanding of Lean Construction principles. The main aim of this study is to develop a conceptual model for a successful dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 97 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…This study concluded that it was necessary to minimize variability caused by unreliable flows (flow activities) and manage the remaining system variability by using effective labor-management strategies. Inefficient information and materials flow could lead to much waste in construction (Bajjou et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study concluded that it was necessary to minimize variability caused by unreliable flows (flow activities) and manage the remaining system variability by using effective labor-management strategies. Inefficient information and materials flow could lead to much waste in construction (Bajjou et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Waste elimination and continuous improvement are integrated throughout the construction cycle, starting from the beginning to the end of the project (Bajjou et al , 2018). They are important for the performance of construction projects during the three stages of the project (input phase, transformation phase, output phase).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Lean philosophy was developed at the beginning of the automotive industry. Nowadays, it is starting to be more integrated into different fields (for example, the construction, health and manufacturing industries, and administration) and is considered as a new way of designing management systems in order to improve process efficiency (Garre et al, 2017;Bajjou & Chafi, 2018d;Bajjou et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Lean Construction (LC) in an innovative way of construction project management aiming at increasing value for clients while reducing waste, improving quality, avoiding workings accidents on constructions sites, as well as preventing negative impact on the environment. [29][30][31][32][33] Regarding the relationship between FA and LC, 71.4% of respondents consider that there is a relationship between both approaches. On the other hand, with the impact of the Covid 19 pandemic, 60.3% of the companies consider that this pandemic will not have an impact on the decision-making process regarding the applicability and integration of AM (see Figure 3 and Table 2).…”
Section: General Aspects Of Concrete Additive Manufacturingmentioning
confidence: 99%